Assessing Audiologists' Exposure, Knowledge, and Attitudes when Working with Individuals Within the Deaf Culture - Cottrell, Chelsea E.; Medwetsky, Larry; Boudreault, Patrick; Easterling, Beth A. (Journal of the American Academy of Audiology, 2021)
Background Historically, the Deaf community and audiologists have had differing views concerning hearing loss intervention. Even so, members of the Deaf community may see an audiologist for a variety of reasons and it is important that audiologists understand how to best work with these individuals. Professional audiological organizations encourage cultural competence when working with different cultures, including the Deaf community.Purpose This study investigates audiologists' current cultural competency and exposure to, knowledge of, and attitudes towards Deaf individuals.Research Design A survey was sent out to 600 audiologists and descriptive analyses was completed.Data Collection and Analysis Study data were managed using REDCap electronic data capture tools and subsequently tabulated for each of the various survey questions.Results Findings indicate that audiologists have relatively limited exposure to this population in a clinical setting, most use interpreters, and most would like to take more ASL courses. Audiologists' attitudes were positive in serving members from the Deaf community.Conclusion Findings suggest that more education on the use of interpreters would be beneficial. Future research may include examining the Deaf community's experience with audiologists, and the impact of exposure and other variables on the knowledge of and interactions with this population.
Keywords: audiology; cultural competency; Deaf Culture; American Sign Language